Comparison of 16S ribosomal RNA hypervariable regions in microbiome studies of anorexia nervosa - Sharma, Arunabh; Andreani, Nadia Andrea; Keller, Lara; Herpertz-Dahlmann, Beate; Seitz, Jochen; Baines, John F.; Dempfle, Astrid (Frontiers in Microbiology, 2025)
IntroductionShort read sequencing of the 16S ribosomal RNA (rRNA) gene targeting specific hypervariable regions is widely employed to study the human gut microbiota. In these studies, the selection of particular 16S rRNA hypervariable regions is a crucial step. However, the results of such studies exhibit significant variability depending on the targeted hypervariable region.MethodsIn this study, we systematically evaluated the performance of hypervariable regions V1V2 and V3V4 in a longitudinal gut microbiome study of adolescent patients with anorexia nervosa (AN) and matched controls.ResultsThe dominant genera, such as Bacteroides H, Faecalibacterium and Phocaeicola A 858004 were consistently detected in both hypervariable regions across timepoints. The within-sample longitudinal alpha diversity measures varied between the regions with the Chao1 index values being higher in the V1V2 region. The overall microbiome profiles based on beta diversity also differed between the regions. Bland–Altman analysis revealed a general lack of strong agreement between the two sequencing methods, except for a few taxa such as Faecalibacterium, Ruminococcus, Roseburia, Turicibacter and Anaerotruncus. While some results were similar across both hypervariable regions, most of the findings were sensitive to the chosen region.ConclusionThis study underscores the importance of primer selection in microbiome studies of AN, as it can influence taxonomic resolution and diversity estimates along with downstream statistical analyses.